Emeritus professors vision about students: learning from older professors - Felipe Trillo Alonso; María Ainoa Zabalza Cerdeiriña; Ana Parada Gañeta (Red U, 2015)
This work is part of a wider investigation developed  in  the  framework  of  the call for R&D of the Spanish Ministry of Science and Innovation which involved several Spanish and foreign universities. Its main objective was to recover the expertise  of  Emeritus  Professors  to make  it  available  to  the  university community. This article presents some data  regarding  beliefs  on  students expressing by 41 Emeritus Professors of  Spanish  and  foreign  universities.